Pembinaan Penyusunan Laporan Keuangan Dan Pemberdayaan Pemasaran Berbasis E-commerce Pada UKM Bank Sampah Mandiri Kota Batam - Dian Efriyenti; Tukino Tukino (Altruis: Journal of Community Services, 2021)
The implementation of community service activities that will be carried out is in the form of fostering the preparation of financial reports and marketing empowerment based on e-commerce for small and medium-sized enterprises of bank sampah Mandiri. Based on the results of interviews in the field, this Mandiri Garbage Bank UKM has problems in marketing production and financial records. The methods used in coaching the SME Bank Sampah Mandiri that will be provided are survey methods, The results of the SME service feel that there is still a need for adjustments to the preparation of financial statements with financial accounting standards for entities without public accountability, there has been a separation of financial reports that have been commonly prepared by SMEs through business profits and personal cash and the availability of SME social media pages that are run by participants and understand it. about what to do with the page to maximize sales.